Digestibilidade aparente do farelo de soja e do milho em dietas para tilápia do Nilo - Cruz, Marta Caroline Silva da (2018)
The present study aimed to evaluate, based on the apparent digestibility coefficients (ADC) of the crude protein (CP) and gross energy (GE), the best level of inclusion of soybean meal (SM) and corn (CO) in diets for Nile tilápia. For ADC reassortments, an assay was performed for each ingredient, where the SM was the first to be evaluated, soon after, the CO. We used 480 specimens of tilapia with average initial weight of 100g, distributed in 24 To obtain reliable ADC's for Nile tilapia, the minimum inclusion level of SM is 18%. For CO, the inclusion level that presented the best results was 24%. tanks, adapted for the collection of feces, with recirculation of water, constant aeration and temperature control, in a completely randomized design with six treatments and four replications, totalizing 20 animals per tank. Different concentrations (6, 12, 18, 24 and 30%) of SM and CO were evaluated in diets for tilapia. The values obtained for SM were 85.45; 88.00; 93.34; 92.04; 92.34% for CP ADC; for GE 78.61; 80.28; 84.25; 81.71 and 81.96%; respectively for treatments with 6, 12, 18, 24 and 30%. For CO, ADC values for CP were 94.70%, 93.26%, 93.20%, 95.16%, 92.69%; for GE 85.46; 83.77; 84.44; 88.66 and 83.99%; respectively for treatments with 6, 12, 18, 24 and 30%. Inclusion values of SM above 18% presented the best ADC of CP and GE for Nile tilapia. For corn, the best results for the digestibility coefficients were with 24% inclusion. To obtain reliable ADC's for Nile tilapia, the minimum inclusion level of SM is 18%. For CO, the inclusion level that presented the best results was 24%.